Prevalence of Frozen Shoulder among Diabetes Patients: A Cross-Sectional Study at a Tertiary Care Center - Manoj Sahu; Mohammad Ilias; Ramesh Pandey; Saumya Saxena; Talha Saad; Nitu Mishra (Journal of Pharmacy and Bioallied Sciences)
Background: Frozen shoulder, also known as adhesive capsulitis, is marked by pain and restricted shoulder movement, with diabetes mellitus being a known risk factor. However, its occurrence in diabetic individuals in health care settings is underreported. Objective: To estimate the occurrence of frozen shoulder among diabetic patients in a tertiary hospital. Methods: This observational study evaluated patients with diabetes for frozen shoulder through clinical diagnosis and imaging. Prevalence was calculated. Results: Frozen shoulder was observed in 11% of diabetic cases, highlighting the need for routine screening in this population. Conclusion: The study emphasizes the importance of screening for frozen shoulder in diabetic patients to ensure early diagnosis and management.